THE EFFECT OF LEARNING MEDIA AND MOTIVATION ON THE RESULTS OF LEARNING DRIBBLING PASSING IN FOOTBALL GAMES IN STUDENTS (INDONESIA) - sahabul adri ar abul; Firmansyah Dlis; Hidayat Humaid (Program Pascasarjana Universitas Negeri Jakarta, 2020)
This study aims to determine: 1) the difference in the effect of visual learning media and audio-visual media on the ability to learn football. 2) the difference in influence between high and low motivation levels on learning outcomes of football. 3) the interaction between learning media and students' motivation on football learning outcomes. This study used an experimental method with a 2 x 2 factorial design. The study population consisted of 530 students and the sample used in this study was 44 people with purposive sampling technique, consisting of 22 high motivation students and 22 low motivation students. The results showed; 1) There is an Influence of Learning Media and Motivation on Learning Outcomes of Dribbling Passing in Football Games on Students The Effect Of Learning Media And Motivation On The Results Of Learning Dribbling Passing In Football Games In Students There are differences in influence between the use of visual media, evident from f count (4.915) smaller F table (4.085). 2) there is a difference in the effect of high motivation and low motivation on learning outcomes football. Evidenced by F count (141.360) smaller from F table (4.085) and (3) There is an interaction between learning media and student learning motivation on learning outcomes, as evidenced by the F count (6,433) smaller F tabel (4.085).